Experimental animal models in traumatic brain injury research: a comprehensive review of methods and outlook - Saidu, Umar Faruk; Bulama, Ibrahim; Onu, Andrew; Abbas, Abdullahi Yahaya; Saidu, Yusuf; Bilbis, Lawal Suleman (International Journal of Scientific Reports, 2024)
Traumatic brain injury (TBI) remains a significant public health concern worldwide, necessitating effective research models to elucidate its pathophysiology and develop therapeutic interventions. Animal models play a crucial role in TBI research, offering valuable insights into injury mechanisms and potential treatments. However, selecting the appropriate model can be challenging due to diverse array of available options and their respective advantages and limitations. In this comprehensive review, we examine four commonly used animal models of TBI: the weight drop, fluid percussion, cortical impact, and blast injury models. Each model is characterized by distinct injury mechanisms, allowing researchers simulate various aspects of TBI pathology. We discuss the unique advantages and disadvantages of each model, providing insights into their applications and considerations for model selection based on research objectives and outcome measures. Furthermore, we highlight emerging directions in TBI modelling, emphasizing the importance of refining and innovating models to replicate the complexity of human TBI. By critically evaluating and understanding the subtlety of different TBI models, researchers can make informed decisions to enhance the translational potential of preclinical TBI research and ultimately improve clinical outcomes for TBI patients.